Tingkat Keterbacaan Ketentuan dan Kebijakan Privasi pada Aplikasi WhatsApp oleh Remaja - Firyal Malihah; Davina Qhina Nashifah; Matanathan Asysam; Geofakta Razali; Johan Rio Pamungkas (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to analyze the readability level of the provisions and privacy policies on the WhatsApp application aimed at teenagers. Teenagers are active users of technology, including instant messaging applications such as WhatsApp, but their understanding of privacy policies is often limited. This research uses a quantitative method using the Flesch-Kincaid readability analysis tool to evaluate the level of difficulty in understanding the WhatsApp privacy policy document. The sample for this study consisted of teenagers in the age range 18 - 22 years. It is hoped that the research results will provide a better understanding of how easy or difficult it is for teenagers to understand WhatsApp's privacy terms and policies, as well as the implications for their privacy and data security. It is hoped that these results can contribute to efforts to increase teenagers' awareness and understanding of the importance of data privacy in using instant messaging applications.